EFFECT OF COMBINATION OF PLYOMETRIC AND SKILL TRAINING IN THE IMPROVEMENT OF SPEED, LEG EXPLOSIVE POWER AND PASSING ABILITY OF THE FEMALE VOLLEYBALL PLAYERS - . K. K, Ravichandra; Rajan, Dr. A.Kaleb; .M.G, Dr.Muniraju (The journal of contemporary issues in business and government, 2022)
The intention of the report was to discovery out the personal effects of the aggregation of PSTG in the development of speed, Leg explosive power and passing quality of school level volleyball game players. 60 volleyball players from the different schools of Bangaluru in Karnataka were designated as capable and their age scope from 14 to 17 years. The dependent were separated into 3 equivalent unit. The 1st group underwent PSTG (n=20), the 2nd group underwent STG (n=20) and the 3rd group acted as the CG they did not exercise any particular training. The designated changeable were measure by the velocity (50mts run test), leg explosive power (vertical jump test) and passing ability (Brady volleyball game test) behavior earlier and later the 12 weeks of activity program. The information was unanalyzed by the analysis of co-variance. The PSTG showed greater improvement in the speed, leg explosive power and passing power than the other three groups of the STG and CG.